The Stuart Period (1603-1714) - Edwards, Ralph; Ramsey, L.G.G . (London The Connoisseur, 1957)
The Jacobean Age - Architecture - Furniture - Painting & Portrait Miniatures - Sculpture - Silver - Pottery, Porcelain & Glass - Domestic Metalwork - Textiles - Costume - Jewellery - Music & musical Instruments - Bookbinding - Printing
Keywords: House of Stuart; 17th Century (1601-1700); 18th Century (1701-1800); Cultural history; Fine art; Architecture; Applied arts; Fashion; Bookbinding; Sculpture; Printing; Musical Instrument; United Kingdom